Risk Factor Analysis and Prevalence of the Non-Alcoholic Fatty Liver Disease in Patients with Type-II Diabetes Mellitus - Sami Ullah, Amjad Ali, Mohammad Hanif, Arjun Kumar, Hafiz ud Din, Roomisa Anis (Pakistan Journal of Medical & Health Sciences, 2022)
Though non-alcoholic fatty liver disease (NAFLD) is associated strongly with type-II diabetes mellitus (T2DM), the NAFLD analysis in patients with Type-II DM remainders an issue. Aim: This analysis was designed to examine the pervasiveness and NAFLD risk factors in T2DM patients. Study Design: A retrospective, cross-sectional study Place and duration: In the department of Medicine, Mardan Medical Complex and Northwest General Hospital & Research Centre Hayatabad, Peshawar for six-months duration from May 2021 to October 2021. Methods: This study includes 420 patients with DM2 presented and treated for glycaemic control. Targeted patients were selected and separated using strict exclusion criteria. Patients with NAFLD (study group) and patients without NAFLD (control group) were divided into two groups. Then, comparison of thirty-four factors amid the 2 groups were done. In addition, NAFLD risk factors multivariate analysis was executed by means of logistic regression. Lastly, the combined predictive indicator (CPI) as well as the analytical significance of the biochemical predictors for NAFLD were assessed by receiver operational characteristic curve (ROC) analysis. Results: The general incidence of NAFLD in this study among DM2 patients was 53.6%. 17 patient target factors were recognised using univariate analysis NAFLD analysis, and eight factors turned out to be important forecasters of NAFLD by means of a binary logistic regression model. Moreover, C-peptide and CPI have augmented analytical importance for NAFLD in patients with T2DM. Conclusion: This analysis delivers a thorough analysis of NAFLD risk factors in subjects with DM2. This information can be cast-off to ensure the effective treatment and timely analysis of NAFLD.